2011
DOI: 10.1007/s11200-010-9030-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of crustal thickness from two gravimetric-isostatic models and CRUST2.0

Abstract: The Mohorovičić discontinuity is the boundary between the Earth's crust and mantle. Several isostatic hypotheses exist for estimating the crustal thickness and density variation of the Earth's crust from gravity anomalies. The goal of this article is to compare the Airy-Heiskanen and Vening Meinesz-Moritz (VMM) gravimetric models for determining Moho depth, with the seismic Moho (CRUST2.0 or SM) model. Numerical comparisons are performed globally as well as for some geophysically interesting areas, such as Fen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Sjöberg and Bagherbandi [10] computed the Moho depths based on solving Moritz's generalization of the Vening-Meinesz inverse problem of isostasy (VMM isostatic model). Bagherbandi and Sjö-berg [11] demonstrated that the VMM Moho depths better agree with the Moho data taken from the global crustal seismic model CRUST2.0 (Bassin et al [12]) than those obtained based on solving the Airy-Heiskanen isostatic model.…”
Section: Introductionmentioning
confidence: 91%
“…Sjöberg and Bagherbandi [10] computed the Moho depths based on solving Moritz's generalization of the Vening-Meinesz inverse problem of isostasy (VMM isostatic model). Bagherbandi and Sjö-berg [11] demonstrated that the VMM Moho depths better agree with the Moho data taken from the global crustal seismic model CRUST2.0 (Bassin et al [12]) than those obtained based on solving the Airy-Heiskanen isostatic model.…”
Section: Introductionmentioning
confidence: 91%
“…Sjöberg and Bagherbandi (2012) demonstrated the advantage of using the combined least-squares method compared to the Airy-Heiskanen model. Bagherbandi and Sjöberg (2011) computed the Moho depths based on solving Moritz's generalization of the Vening-Meinesz inverse problem of isostasy (VMM isostatic model). They demonstrated that the VMM Moho depths generally better agree with CRUST2.0 data than those obtained from using the Airy-Heiskanen isostatic model.…”
Section: Introductionmentioning
confidence: 99%